NGHIÊN CỨU VỀ TOURMALIN Ở HOẰNG HÓA, THANH HÓA - Bình, Nguyễn Văn (Vietnam Journal of Earth Sciences, 2017)
The paper presents some characteristcs of bigcrystals of black tourmaline - a new found in HoangHoa district (Thanh Hoa province). The blacktourmaline was found as a big crystals on the pegmatite bodies and quartz vein. The study on tourmaline from Hoang Truong pegmatite and quartz vein, by chemical analysis, X-ray diffraction allowed to indicate that black tourmaline of the Hoang Truong pegmatite and quartz vein was mainly belongs to schorl.